Antibacterial and wound healing applications of curcumin in micro and nano-scaffolds based on chitosan, cellulose, and collagen: Antibacterial and wound healing applications of curcumin in micro and nano-scaffolds - Alavi, Mehran; Moetasam Zorab, Musa; Ashengroph, Morahem; Aljelehawy, Qassim Hassan Aubais; Kahrizi, Danial (Cellular and Molecular Biology, 2022)
About 80% higher risk of amputation resulted from microbial infection was indicated for patients with diabetic foot ulcers (DFUs). Micro and nano-scaffolds made of natural polymers specifically cellulose, chitosan, and collagen can donate the biocompatibility, biodegradability, and bioavailability properties appropriate to accelerate wound closure before microbial biofilm formation. Antimicrobial activity of these wound dressings can be improved by incorporation of bioactive compounds extracted from medicinal plant species such as curcumin. Low water solubility and poor bioavailability are recognized as two main disadvantages of curcumin, lipophilic phytopolyphenol, which could be controlled by targeted polymeric micro and nano-scaffolds. Consequently, this review has discussed the capacity and challenges of these types of formulations according to recent investigations.